High-solid three-coat-one-bake mid-coat for automobiles based on waterborne acrylic resin and its application

Through the combination of water-based acrylic resin and inorganic rheological additives, the solid content and construction performance of water-based three-coat-one-bake coatings are improved, solving the problems of low solid content, high VOC, poor appearance and insufficient stone chip resistance in traditional coatings, and achieving a coating effect that takes both environmental protection and performance into consideration.

CN116925610BActive Publication Date: 2025-09-30NIPPON PAINT CHINA
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202210372556.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-04-11
Publication Date
2025-09-30
Estimated Expiration
2042-04-11

AI Technical Summary

Technical Problem

In the existing water-based three-coat-one-bake coating system, the mid-coat has low solid content, high VOC content, poor appearance, and insufficient stone chip resistance, which cannot meet environmental protection and performance requirements.

Method used

A high-solid three-coat-one-bake mid-coat based on water-based acrylic resin is used. Through the combination of specific component ratios and inorganic rheological additives, unique rheological properties are formed to improve the atomization and leveling effects of the coating, reduce VOC content, and enhance the appearance and construction performance of the coating.

Benefits of technology

The coating has low VOC emissions, excellent appearance and good construction applicability under low film thickness conditions, and the coating has excellent stone chip resistance, which solves the limitations of traditional coatings.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003589403700000101
    Figure BDA0003589403700000101
  • Figure BDA0003589403700000111
    Figure BDA0003589403700000111
  • Figure BDA0003589403700000121
    Figure BDA0003589403700000121
Patent Text Reader

Abstract

The present invention discloses a high-solids, three-coat, one-bake mid-coat for automobiles based on a water-based acrylic resin. The mid-coat is characterized by being a single-component paint and comprising, by weight, 10-25 parts of a water-based acrylic emulsion, 5-15 parts of a water-based polyurethane dispersion B, 5-15 parts of a water-based polyurethane dispersion C, and 30.1-70.4 parts of additives. The additives include 0.1-0.4 parts of an inorganic rheological modifier. The water-based polyurethane dispersion B has a hydroxyl value of less than 5 mgKOH / g and an acid value of 20-35 mgKOH / g; the water-based polyurethane dispersion C has a hydroxyl value of 110-160 mgKOH / g. The mid-coat exhibits high base solids, low coating consumption, and low VOC emissions, while maintaining excellent coating appearance, superior mechanical properties, and ease of application. The present invention also discloses applications of the mid-coat.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of coatings, and more particularly to a high-solid, three-coat, one-bake intermediate coating for automobiles based on a water-based acrylic resin and its application. Background Art

[0002] Waterborne automotive coatings are a multi-component material composed of water-emulsifiable, water-dispersible, and water-soluble polymers as film-forming materials, water as the primary dispersion medium, and organic solvents as cosolvents. Since 2009, waterborne automotive coatings have been actively used and promoted by major automotive OEMs in China, as they comply with government regulations on low-volatile organic compound (VOC) coatings and align with public awareness of green and environmentally friendly trends.

[0003] In traditional waterborne, three-coat, two-bake automotive coating systems, the midcoat has a film thickness of 30 to 40 microns and requires a high-temperature baking process of 140°C to achieve curing and crosslinking of the midcoat, which consumes a lot of materials and energy. The waterborne, three-coat, one-bake coating system significantly reduces the film thickness of the midcoat, with the topcoat film thickness ranging from 12 to 18 microns. It also eliminates the need for a high-temperature baking process and only requires a 4-8 minute flash-drying period at room temperature before the topcoat can be applied.

[0004] The limitations of the conventional water-based three-coat-one-bake mid-coat in the current industry are mainly reflected in the following points: First, the solid content of conventional mid-coat is relatively low, so the amount of paint consumed per vehicle is relatively high; second, the organic compound content (VOC) of conventional mid-coat is relatively high, and most of them cannot meet the latest national VOC low standard; third, there are currently a few mid-coats that can achieve a higher solid content, but their appearance, that is, the overall coating's flatness, visual fullness, and appearance data indicators (long wave, short wave, distinctness of image DOI, etc.) cannot reach a satisfactory level; fourth, the current conventional three-coat-one-bake products, due to the low thickness of the mid-coat film, cannot achieve good anti-stone impact performance, and a large amount of paint falling off in the stone impact test is common. Summary of the Invention

[0005] In view of the deficiencies in the above-mentioned prior art, the object of the present invention is to provide a high-solids three-coat-one-bake mid-coat for automobiles based on water-based acrylic acid and its application, so as to at least solve the problems existing in existing mid-coats, such as the difficulty in achieving low VOC emissions, excellent appearance, good construction applicability (anti-sagging and anti-pinhole properties), and excellent mechanical properties (especially stone chip resistance) under the conditions of low film thickness and high solids.

[0006] To achieve the first goal mentioned above:

[0007] In one aspect, the present invention provides a high-solid, three-coat, one-bake mid-coat for automobiles based on a waterborne acrylic resin. The mid-coat is a single-component paint and comprises the following components in parts by weight:

[0008] 10-25 parts of aqueous acrylic emulsion, 5-15 parts of aqueous polyurethane dispersion B, 5-15 parts of aqueous polyurethane dispersion C and 30.1-70.4 parts of additives;

[0009] in:

[0010] The additive contains 0.1-0.4 parts of inorganic rheological additive;

[0011] The aqueous polyurethane dispersion B has a solid content of 32% to 42%, a hydroxyl value of <5 mgKOH / g, an acid value of 20 to 35 mgKOH / g, a number average molecular weight of >10,000, a resin particle size of 30 to 100 nm, and a dispersion pH of 7.0 to 8.5;

[0012] The solid content of the aqueous polyurethane dispersion C is 34% to 44%, the hydroxyl value is 110 to 160 mgKOH / g, and the pH value of the dispersion is 7.0 to 8.8.

[0013] Furthermore, the water-based acrylic emulsion has a solid content of 45% to 55%, a hydroxyl value of 5 to 20 mgKOH / g, an acid value of 10 to 25 mgKOH / g, a resin particle size of 110 to 160 nm, and an emulsion pH of 7.5 to 9.0.

[0014] Furthermore, the aqueous acrylic emulsion is prepared from acrylic acid monomers, acrylate monomers, methacrylate monomers and vinyl monomers through free radical emulsion polymerization.

[0015] Furthermore, the preparation of the aqueous acrylic emulsion specifically comprises the following steps:

[0016] Premixing acrylic monomers, part of acrylic ester monomers, part of methacrylic ester monomers, and part of vinyl monomers in the presence of water and an emulsifier to obtain a monomer premix solution I;

[0017] Premixing the remaining acrylic acid ester monomer, the remaining methacrylic acid ester monomer, and the remaining vinyl monomer in the presence of water and an emulsifier to obtain a monomer premix solution II;

[0018] Under nitrogen protection, the monomer premix solution I is subjected to a prepolymerization reaction and the pH is adjusted to 7.5-9.0;

[0019] The monomer premix liquid II is continuously added to the resultant to carry out polymerization reaction, and the pH is adjusted to 7.5-9.0 to obtain the aqueous acrylic emulsion.

[0020] Furthermore, the aqueous polyurethane dispersion B is prepared by reacting materials including polyester polyol, non-aromatic diisocyanate, and triol containing a carboxyl functional group.

[0021] Furthermore, the preparation of the aqueous polyurethane dispersion B specifically includes the following steps:

[0022] Synthetic polyester polyols with a hydroxyl value of 25 to 75 mgKOH / g, an acid value of <1 mgKOH / g, and a number average molecular weight of 1500 to 4000;

[0023] Under nitrogen protection, the polyester polyol and the triol containing a carboxyl functional group are mixed, and then reacted with a non-aromatic diisocyanate until the NCO equivalent reaches 800 to 1100; after neutralization, a polyurethane prepolymer dispersion is obtained;

[0024] Under nitrogen protection, the polyurethane prepolymer dispersion is subjected to a chain extension reaction to obtain the aqueous polyurethane dispersion B.

[0025] Furthermore, the inorganic rheological additive is an inorganic sheet silicate.

[0026] Furthermore, the auxiliary agent also contains 5 to 10 parts of a membrane-forming solvent.

[0027] Furthermore, the additive further comprises 0.5 to 2 parts of an organic rheological additive, 2 to 4 parts of a defoaming agent and 1 to 3 parts of a dispersant.

[0028] Furthermore, the mid-coat paint also contains 5 to 15 parts of amino resin.

[0029] Furthermore, the mid-coat paint also contains 15 to 25 parts of pigments and fillers.

[0030] Furthermore, the mid-coat paint also contains 5 to 20 parts of water.

[0031] Furthermore, the crystal structure of the inorganic sheet silicate is trioctahedral, and the basic structural unit morphology is an oblate cylindrical thin-plate crystal with a front diameter of 20 to 40 nm and a negative charge, and a side thickness of 0.5 to 2.5 nm and a positive charge.

[0032] In another aspect, the present invention provides use of the above-mentioned high-solid three-coat-one-bake intermediate paint for automobiles in forming an automobile coating.

[0033] Furthermore, the application includes the following steps:

[0034] Applying the mid-coat on the electrophoretic primer coating;

[0035] Flash dry to form a midcoat.

[0036] The beneficial effects of the present invention are as follows:

[0037] The acrylic resin and two specific waterborne polyurethane dispersions in the high-solids, three-coat, one-bake midcoat for automotive applications, combined with selected inorganic rheological additives, impart unique rheological properties to the midcoat. This results in a coating system with improved atomization, leveling, and anti-sagging properties, resulting in a superior appearance. Furthermore, the midcoat system exhibits a higher solids content than conventional three-coat, one-bake systems and a lower VOC content. Furthermore, while maintaining a higher solids content, the present invention can achieve the same or even superior appearance and application performance as conventional low-solids systems. DETAILED DESCRIPTION

[0038] In order to explain the present invention more clearly, the present invention is further described below in conjunction with preferred embodiments. Those skilled in the art should understand that the following specific description is illustrative rather than restrictive and should not be used to limit the scope of protection of the present invention.

[0039] One embodiment of the present invention provides a high-solid, three-coat, one-bake mid-coat for automobiles based on a water-based acrylic resin. The mid-coat is a single-component paint and comprises the following components in parts by weight:

[0040] 10-25 parts of aqueous acrylic emulsion, 5-15 parts of aqueous polyurethane dispersion B, 5-15 parts of aqueous polyurethane dispersion C and 30.1-70.4 parts of additives;

[0041] in:

[0042] The additive contains 0.1 to 0.4 parts of an inorganic rheological additive;

[0043] The aqueous polyurethane dispersion B has a solid content of 32% to 42%, a hydroxyl value of <5 mgKOH / g, an acid value of 20 to 35 mgKOH / g, a number average molecular weight of >10,000, a resin particle size of 30 to 100 nm, and a dispersion pH of 7.0 to 8.5;

[0044] The solid content of the aqueous polyurethane dispersion C is 34% to 44%, the hydroxyl value is 110 to 160 mgKOH / g, and the pH value of the dispersion is 7.0 to 8.8.

[0045] In a preferred example, the solid content (weight solids, %) of the aqueous acrylic emulsion is 45% to 55%, the hydroxyl value (based on solid content) is 5 to 30 mgKOH / g, the acid value (based on solid content) is 10 to 30 mgKOH / g, the resin particle size is 110 to 160 nm, and the emulsion pH is 7.5 to 9.0. The aqueous acrylic emulsion under the above conditions can better help improve the overall performance of the formula, achieve a higher coating solid content and better coating appearance, sagging, pinhole and stone chip resistance. If the emulsion solid content is too high, the stability of the resin emulsion itself will deteriorate. If the emulsion solid content is too low, the solid content of the coating will decrease; if the resin hydroxyl value is too high, the pinhole performance will deteriorate. If the resin hydroxyl value is too low, the coating hardness will decrease; if the acid value is too high, the water resistance and long-term weather resistance will deteriorate. If the acid value is too low, the storage stability of the resin itself will deteriorate. Exemplarily, the hydroxyl value of the aqueous acrylic emulsion (based on solid content) includes but is not limited to 5-10 mgKOH / g, 10-15 mgKOH / g, 15-20 mgKOH / g, 15-25 mgKOH / g, 20-25 mgKOH / g, 25-30 mgKOH / g, etc.; Exemplarily, the acid value of the aqueous acrylic emulsion (based on solid content) includes but is not limited to 10-15 mgKOH / g, 10-20 mgKOH / g, 15-20 mgKOH / g, 15-25 mgKOH / g, 20-25 mgKOH / g, 20-30 mgKOH / g, 25-30 mgKOH / g, etc. Exemplarily, the amount of aqueous acrylic emulsion used includes but is not limited to 15-25 parts, 16-23 parts, 16-20 parts, 16-19 parts, 19-25 parts, 19-23 parts, 19-20 parts, 20-25 parts, 20-23 parts, etc.

[0046] In some examples, the aqueous acrylic emulsion is prepared from acrylic monomers, acrylate monomers, methacrylate monomers, and vinyl monomers through free radical emulsion polymerization.

[0047] In a preferred example, the preparation of the aqueous acrylic emulsion specifically includes the following steps:

[0048] Premixing acrylic monomers, part of acrylic ester monomers, part of methacrylic ester monomers, and part of vinyl monomers in the presence of water and an emulsifier to obtain a monomer premix solution I;

[0049] Premixing the remaining acrylic acid ester monomer, the remaining methacrylic acid ester monomer, and the remaining vinyl monomer in the presence of water and an emulsifier to obtain a monomer premix solution II;

[0050] Under nitrogen protection, the monomer premix solution I is subjected to a prepolymerization reaction and the pH is adjusted to 7.5-9.0;

[0051] The monomer premix liquid II is continuously added to the resultant to carry out polymerization reaction, and the pH is adjusted to 7.5-9.0 to obtain the aqueous acrylic emulsion.

[0052] In a specific example, the preparation of the aqueous acrylic emulsion includes the following steps:

[0053] 1) Preparation of monomer premix solution I:

[0054] To an open container, water (35 parts, by weight, the same below), emulsifier (0.5 parts), acrylic acid monomer (2.5 parts), acrylate monomer (30 parts), methacrylate monomer (30 parts), and vinyl monomer (2 parts) were added in sequence and mixed at high speed to obtain a monomer premix solution I;

[0055] For example, the acrylic monomers include, but are not limited to, one or more selected from acrylic acid and methacrylic acid.

[0056] Illustratively, the acrylic acid ester monomer is selected from one or more of n-butyl acrylate, isobutyl acrylate, tert-butyl acrylate, hydroxyethyl acrylate, and hydroxypropyl acrylate.

[0057] Exemplarily, the methacrylate monomer is selected from one or more of methyl methacrylate, ethyl methacrylate, allyl methacrylate, and butyl methacrylate;

[0058] For example, the vinyl monomer is selected from one or more of styrene and divinylbenzene.

[0059] Illustratively, the emulsifier is selected from one or more of potassium laurate, potassium stearate, potassium oleate, sodium decyl sulfate, sodium lauryl sulfate, sodium dodecylbenzenesulfonate, sodium rosinate, and the like.

[0060] 2) Preparation of monomer premix II:

[0061] To another open container, water (30 parts), emulsifier (0.5 parts), acrylate monomer (30 parts), methacrylate monomer (25 parts), and vinyl monomer (14.5 parts) were added in sequence and mixed at high speed to obtain monomer premix II;

[0062] Illustratively, the acrylic acid ester monomer is selected from one or more of n-butyl acrylate, isobutyl acrylate, tert-butyl acrylate, and isooctyl acrylate.

[0063] Illustratively, the methacrylate monomer is selected from one or more of methyl methacrylate, ethyl methacrylate, allyl methacrylate, and butyl methacrylate.

[0064] For example, the vinyl monomer is selected from one or more of styrene and divinylbenzene.

[0065] Illustratively, the emulsifier is selected from one or more of potassium laurate, potassium stearate, potassium oleate, sodium decyl sulfate, sodium lauryl sulfate, sodium dodecylbenzenesulfonate, sodium rosinate, and the like.

[0066] 3) Synthesis and preparation of water-based acrylic emulsion

[0067] Under nitrogen protection, water (25.35 parts), emulsifier (0.5 parts), initiator (0.15 parts), and monomer premix I (37.5 parts) were added to the reactor in sequence, and the mixture was stirred and heated to 80°C for 2 to 3 hours.

[0068] A pH regulator (0.4 parts) was added to the reactor to adjust the pH of the mixture to 7.5-9.0;

[0069] Under nitrogen protection, monomer premix II (36 parts) was added to the reactor and the reaction temperature was maintained at 80° C. for 2 to 3 hours.

[0070] A pH regulator (0.1 part) was added to the reactor to adjust the pH of the mixture to 7.5-9.0;

[0071] The temperature of the reactor was lowered to below 35° C., sterilized, filtered, and discharged to obtain a water-based acrylic emulsion.

[0072] Exemplarily, the emulsifier is an anionic or nonionic emulsifier, selected from one or more of potassium laurate, potassium stearate, potassium oleate, sodium decyl sulfate, sodium lauryl sulfate, sodium dodecylbenzenesulfonate, sodium rosinate, and the like.

[0073] Exemplarily, the initiator is a water-soluble initiator selected from one or more of ammonium persulfate, sodium persulfate, potassium persulfate, tert-butyl hydroperoxide, and the like.

[0074] Exemplarily, the pH adjuster is an organic amine, selected from one or more of N,N-dimethylethanolamine, N,N-diethylethanolamine, 2-(dimethyl)amino-2-methyl-1-propanol, triethylamine, and the like.

[0075] The outer molecular chain structure of the water-based acrylic emulsion resin particles described in this embodiment contains negatively charged carboxyl groups derived from structural units such as acrylic acid and methacrylic acid. These groups form a three-dimensional complex in the aqueous phase through weak interactions such as electrostatic interactions with the lamellae units of the inorganic silicate additive in the formulation. Under weak external shear forces, the presence of this complex structure results in a higher apparent viscosity, preventing separation and sedimentation between the coating components and improving the coating's storage stability. Under external high shear forces (such as construction atomization), the complex structure is rapidly broken down, resulting in a decrease in the apparent viscosity of the system. This facilitates the formation of smaller and more evenly distributed atomized particles during spray application, further improving the leveling of the wet film and reducing surface roughness, resulting in a more uniform and smooth coating surface and excellent coating appearance. Furthermore, the reduction in atomized particle size during spray application increases the specific surface area of ​​the atomized particles, facilitating the volatilization of solvent components in the coating during application, reducing the solvent content of the wet film and improving the synergy and balance of the volatilization of solvent components with different volatilization rates from the wet film. This reduces solvent residue in the wet film and reduces the occurrence of construction defects such as pinholes and bubbles in the coating. After the high shear atomization phase, the shear force on the system is reduced, and the destroyed complex structure can be quickly rebuilt and restored under electrostatic forces. The apparent viscosity of the system rises again, effectively preventing vertical sagging and flow of the wet film and reducing the probability of construction defects.

[0076] Exemplarily, the inorganic rheological modifier is an inorganic sheet silicate. Its chemical elements include, but are not limited to, silicon, magnesium, lithium, and sodium. Its typical crystal structure is trioctahedral, and its basic structural unit is an oblate cylindrical crystalline lamella with a front diameter of 20 to 40 nm, negatively charged, and a side thickness of 0.5 to 2.5 nm, positively charged.

[0077] Furthermore, under the above conditions, the structural units of the inorganic sheet silicate aggregate into a solid powder through interlamellar interactions. When the solid powder is dispersed and added to water, water molecules gradually penetrate into the areas between the structural unit lamellae, undergoing ion exchange and hydration with the existing sodium ions and other ions between the lamellae. This causes the distance between the lamellae to gradually increase, the aggregate to swell, and ultimately the aggregate structure to break apart, separating into individual lamellae-like structural units. Because the front of the lamellae units has a negative charge and the side has a positive charge, the front of the lamellae attracts the side of the other lamellae through electrostatic forces, forming a "house of cards"-like three-dimensional structure with front / side connections. The formed "house of cards" structure can undergo a reversible "dissociation-reconstitution-dissociation" structural morphology transformation under the action of external forces, thus endowing the system with unique rheological properties, effectively improving the system's stability and reducing the occurrence of phenomena such as flocculation and sedimentation.

[0078] Preferably, the exemplary inorganic rheological additives include but are not limited to LAPONITE RD (purchased from BYK Chemical (China) Co., Ltd.), One or more of W2N (available from Leifus (Shanghai) Chemical Trading Co., Ltd.), etc. Exemplary addition amounts of inorganic rheological additives include, but are not limited to, 0.05-0.15 parts, 0.1-0.2 parts, 0.1-0.3 parts, 0.2-0.4 parts, 0.25-0.4 parts, etc.

[0079] The water-based acrylic emulsion has a solids content (weight solids, %) of 45% to 55%, which helps increase the base solids of the midcoat (>40%), exceeding the typical three-coat, one-bake midcoat for automotive applications (≤40%). While excessively high solids content typically increases coating viscosity, resulting in poor atomization during application and poor wet film leveling, leading to a reduced coating appearance or application defects. However, because the three-dimensional complex formed by the lamellar units of the water-based acrylic emulsion and the inorganic silicate rheological modifier in the aqueous phase exhibits a rapid and reversible "dissociation-reconstitution-dissociation" structural morphological transition, the midcoat's apparent viscosity is rapidly reduced under high shear forces during atomization, forming uniform, small-sized atomized particles. This effectively improves spray atomization, allowing the high-solids (>40%) midcoat to maintain excellent coating appearance with fewer application defects such as pinholes and bubbles.

[0080] In the above technical solution, the aqueous polyurethane dispersion B is a macromolecular resin with high molecular weight and low hydroxyl content, has good elongation and tensile strength, and is difficult to undergo chemical cross-linking reaction with other components during the coating baking and curing (130-150°C), thereby giving the mid-coat coating good flexibility and enhancing the overall mechanical properties of the coating such as stone chip resistance and impact resistance. The amount of exemplary aqueous polyurethane dispersion B includes but is not limited to 7-15 parts, 7-14 parts, 7-12 parts, 7-11 parts, 7-10 parts, 7-9 parts, 9-14 parts, 9-12 parts, 9-11 parts, 9-10 parts, 10-14 parts, 10-12 parts, 10-11 parts, 11-14 parts, 11-12 parts, 12-14 parts, etc.

[0081] The aqueous polyurethane dispersion B may be obtained from the prior art. For example, its preparation may be obtained by referring to the method disclosed in publication number CN104745062A.

[0082] In a preferred example, the preparation of the aqueous polyurethane dispersion B specifically includes the following steps:

[0083] Synthetic polyester polyols with a hydroxyl value of 25 to 75 mgKOH / g, an acid value of <1 mgKOH / g, and a number average molecular weight of 1500 to 4000;

[0084] Under nitrogen protection, the polyester polyol and the triol containing a carboxyl functional group are mixed, and then reacted with a non-aromatic diisocyanate until the NCO equivalent reaches 800 to 1100; after neutralization, a polyurethane prepolymer dispersion is obtained;

[0085] Under nitrogen protection, the polyurethane prepolymer dispersion is subjected to a chain extension reaction to obtain the aqueous polyurethane dispersion B.

[0086] In a specific example, the preparation of the aqueous polyurethane dispersion B includes the following steps:

[0087] (1) Synthesis and preparation of polyester polyols:

[0088] Under nitrogen protection, neopentyl glycol (7.5 parts), 1,6-hexanediol (38.5 parts), and 1,6-hexanediol (54 parts) were added to the reactor in sequence, and the temperature was raised to 120° C. until the raw materials melted;

[0089] After the raw materials are completely melted and mixed, continue stirring and heat to 160°C, hold for 1 hour, and then continue to heat to 230°C for 5 hours; during the heat preservation at 230°C, regularly test the acid value until the acid value drops below 1mgKOH / g;

[0090] The temperature is lowered to below 80°C to obtain polyester polyol.

[0091] The prepared polyester polyol has a hydroxyl value of 25-75 mgKOH / g, an acid value of less than 1 mgKOH / g, and a number average molecular weight of 1500-4000.

[0092] (2) Synthesis and preparation of polyurethane prepolymer dispersion:

[0093] Under nitrogen protection, the polyester polyol prepared above (34 parts) and the triol containing a carboxyl functional group (2.5 parts) were added to the reactor in sequence, and the mixture was stirred and heated to 80°C;

[0094] While maintaining the reaction temperature at 80°C, add non-aromatic diisocyanate (12 parts) and continue the reaction at 80°C until the NCO equivalent reaches 800-1100;

[0095] The temperature was lowered to 50° C., and triethylamine (2 parts) was added for neutralization. After sufficient neutralization, water (49.5 parts) was added to obtain a polyurethane prepolymer dispersion (NCO-terminated).

[0096] For example, the triol containing a carboxyl functional group is selected from one or more of trimethylol propionic acid (DMPA) and trimethylol butyric acid (DMBA).

[0097] For example, the non-aromatic diisocyanate is selected from one or more of isophorone diisocyanate (IPDI), hexamethylene diisocyanate (HDI), trimethylhexamethylene diisocyanate (TMDI), and dicyclohexylmethane diisocyanate (HMDI).

[0098] (3) Synthesis and preparation of polyurethane dispersion B:

[0099] Under nitrogen protection, the polyurethane prepolymer dispersion (83.2 parts), ethylenediamine (0.8 parts), and water (16 parts) prepared above were added to the reactor in sequence, and the mixture was stirred and heated to 60° C. for constant temperature reaction for 1 to 2 hours until the prepolymer chain extension reaction was completed;

[0100] The temperature was lowered to 40° C., and the mixture was filtered and discharged to obtain aqueous polyurethane dispersion B.

[0101] In the technical solution of this embodiment, the water-based polyurethane dispersion C has a high content of hydroxyl groups, and can effectively undergo chemical cross-linking reaction with the cross-linking resin during the coating baking and curing process (130-150°C), constructing a three-dimensional cross-linked network structure, and enhancing the hardness, water resistance, and moisture resistance of the coating; at the same time, the presence of a large number of hydroxyl groups will also form chemical bonding and hydrogen bonding and other force connection points between the coating interfaces, increase the adhesion between the coatings, and also have a certain improvement and enhancement effect on the stone impact resistance of the overall coating.

[0102] Exemplarily, the aqueous polyurethane dispersion C is selected from U 2750 (purchased from Covestro (China) Co., Ltd.), U 2755 / 1 (purchased from Covestro (China) Co., Ltd.), U 2766 (available from Covestro (China) Co., Ltd.) and other resin dispersions. Exemplary amounts of the aqueous polyurethane dispersion C include, but are not limited to, 6-15 parts, 6-13 parts, 6-11 parts, 6-10 parts, 6-9 parts, 9-13 parts, 9-11 parts, 9-10 parts, 10-13 parts, 10-11 parts, 11-13 parts, and the like.

[0103] Illustratively, the amino resin described in the present invention is a partially methylated melamine-type amino resin, which contains active reaction groups such as imino groups, hydroxymethyl groups, and methylated groups in its molecular structure. It can undergo chemical cross-linking reaction with the hydroxyl groups of the above-mentioned aqueous polyurethane dispersion C, providing the coating with properties such as hardness, water resistance, and chemical resistance.

[0104] Furthermore, the additives of the mid-coat also include 0.5 to 2 parts of an organic rheological additive, 2 to 4 parts of a defoaming agent, and 1 to 3 parts of a dispersant.

[0105] Furthermore, the mid-coat paint also contains 5 to 20 parts of water.

[0106] Furthermore, the mid-coat paint further comprises 5 to 15 parts of amino resin. Exemplarily, the amino resin is selected from 325 (purchased from Allnex Resins (China) Co., Ltd.), 327 (purchased from Allnex Resins (China) Co., Ltd.), 072 (purchased from BASF Applied Chemicals Co., Ltd.), 073 (purchased from BASF Applied Chemicals Co., Ltd.) or one or more thereof.

[0107] Furthermore, the mid-coat paint further comprises 15 to 25 parts of pigments and fillers. For example, the pigments and fillers of the present invention are selected from one or more of titanium dioxide, talc, ultrafine barium sulfate, carbon black, fumed silica, iron oxide, and the like.

[0108] Furthermore, the additives for the mid-coat further include 5 to 10 parts of a film-forming solvent. For example, the film-forming solvent of the present invention is selected from one or more of ethylene glycol butyl ether, ethylene glycol hexyl ether, ethylene glycol isooctyl ether, diethylene glycol ethyl ether, diethylene glycol butyl ether, propylene glycol butyl ether, dipropylene glycol butyl ether, dipropylene glycol methyl ether, dipropylene glycol dimethyl ether, ethanol, n-propanol, isopropanol, n-butanol, and isooctyl alcohol.

[0109] Furthermore, the additive further comprises 0.5 to 2 parts of an organic rheological additive. For example, the organic rheological additive of the present invention is selected from one or more of alkali-swellable acrylic and polyamide wax rheological additives.

[0110] Furthermore, the organic rheological additive is selected from AS 1130 (purchased from BASF New Materials Co., Ltd.), P2100W (purchased from Deqian (Shanghai) Chemical Co., Ltd.), AQH-633E (purchased from Kusunoki Chemicals Co., Ltd.), AQH-810 (available from Kusunoki Chemicals Co., Ltd.) and the like.

[0111] Furthermore, the auxiliary agent also contains 2 to 4 parts of defoaming agent. Exemplarily, the defoaming agent of the present invention is selected from ST 2400 (purchased from BASF New Materials Co., Ltd.), 104BC (purchased from Evonik (China) Co., Ltd.), One or more of FOAMEX 805N (purchased from Evonik (China) Co., Ltd.), BYKETOL-WS (purchased from BYK Chemical (China) Co., Ltd.), BYK-011 (purchased from BYK Chemical (China) Co., Ltd.), etc.

[0112] Furthermore, the auxiliary agent also contains 1 to 3 parts of a dispersant. The dispersant of the present invention is selected from DISPERBYK-192 (purchased from BYK Chemical (China) Co., Ltd.), DISPERBYK-190 (purchased from BYK Chemical (China) Co., Ltd.), ULTRA PA 4550 (purchased from BASF New Materials Co., Ltd.), ULTRAPX4575 (purchased from BASF New Materials Co., Ltd.), DISPERS 760W (purchased from Evonik (China) Co., Ltd.), DISPERS 755W (purchased from Evonik (China) Co., Ltd.), Gen 1253 (purchased from Guangzhou Songwei Trading Co., Ltd.) and the like.

[0113] Based on the above description of the technical solution, the high-solid three-coat and one-bake intermediate paint for automobiles described in this embodiment can help solve problems such as excessive paint consumption per single body during automobile body painting, high VOC emissions, urgent need to improve the appearance of the paint, and the need to improve stone impact resistance.

[0114] In a specific embodiment of the present invention, there is also provided the use of the above-mentioned high-solid three-coat-one-bake intermediate paint for automobiles based on water-based acrylic resin in forming an automobile coating.

[0115] Exemplarily, the application specifically includes the following steps:

[0116] The mid-coat is applied on the electrophoretic primer coating and flash-dried to form a mid-coat coating.

[0117] Furthermore, the application includes the following steps:

[0118] The mid-coat paint is applied to form the second coating layer in the following multi-coat structure:

[0119] 1) depositing an electrodeposition coating composition (electrophoretic paint) on a substrate and baking and curing it (at 160-190° C.) to form a first coating layer;

[0120] 2) applying the intermediate coating to the surface of the first coating and flash-drying at room temperature to form a second coating;

[0121] 3) applying a coating composition (paint) containing a coloring pigment to the surface of the second coating layer, and pre-baking and dehydrating the coating layer (at 60-80° C.) to form a third coating layer;

[0122] 4) applying a colorless and transparent coating composition (varnish) on the surface of the third coating layer, baking and curing (130-150° C.) to form a fourth coating layer.

[0123] Furthermore, the "flash drying" mentioned above refers to the process in which the volatile components in the coating composition applied to the surface of the previous coating gradually evaporate over a period of time under room temperature conditions.

[0124] Furthermore, the "room temperature condition" refers to 15 to 30° C., and the "period of time" refers to 2 to 20 minutes.

[0125] The technical solution of the present invention is described below with reference to some specific embodiments:

[0126] Unless otherwise specified, the aqueous acrylic emulsion used in the following examples was prepared by the following method:

[0127] The preparation of the aqueous acrylic emulsion comprises the following steps:

[0128] 1) Preparation of monomer premix solution I:

[0129] To an open container, water (35 parts, by weight, the same below), emulsifier (0.5 parts), acrylic acid monomer (2.5 parts), acrylate monomer (30 parts), methacrylate monomer (30 parts), and vinyl monomer (2 parts) were added in sequence and mixed at high speed to obtain a monomer premix solution I;

[0130] For example, the acrylic monomers include, but are not limited to, one or more selected from acrylic acid and methacrylic acid.

[0131] Illustratively, the acrylic acid ester monomer is selected from one or more of n-butyl acrylate, isobutyl acrylate, tert-butyl acrylate, hydroxyethyl acrylate, and hydroxypropyl acrylate.

[0132] Exemplarily, the methacrylate monomer is selected from one or more of methyl methacrylate, ethyl methacrylate, allyl methacrylate, and butyl methacrylate;

[0133] For example, the vinyl monomer is selected from one or more of styrene and divinylbenzene.

[0134] Illustratively, the emulsifier is selected from one or more of potassium laurate, potassium stearate, potassium oleate, sodium decyl sulfate, sodium lauryl sulfate, sodium dodecylbenzenesulfonate, sodium rosinate, and the like.

[0135] 2) Preparation of monomer premix II:

[0136] To another open container, water (30 parts), emulsifier (0.5 parts), acrylate monomer (30 parts), methacrylate monomer (25 parts), and vinyl monomer (14.5 parts) were added in sequence and mixed at high speed to obtain monomer premix II.

[0137] Illustratively, the acrylic acid ester monomer is selected from one or more of n-butyl acrylate, isobutyl acrylate, tert-butyl acrylate, and isooctyl acrylate.

[0138] Illustratively, the methacrylate monomer is selected from one or more of methyl methacrylate, ethyl methacrylate, allyl methacrylate, and butyl methacrylate.

[0139] For example, the vinyl monomer is selected from one or more of styrene and divinylbenzene.

[0140] Illustratively, the emulsifier is selected from one or more of potassium laurate, potassium stearate, potassium oleate, sodium decyl sulfate, sodium lauryl sulfate, sodium dodecylbenzenesulfonate, sodium rosinate, and the like.

[0141] 3) Synthesis and preparation of water-based acrylic emulsion

[0142] Under nitrogen protection, water (25.35 parts), emulsifier (0.5 parts), initiator (0.15 parts), and monomer premix I (37.5 parts) were added to the reactor in sequence, and the mixture was stirred and heated to 80°C for 2 to 3 hours.

[0143] A pH regulator (0.4 parts) was added to the reactor to adjust the pH of the mixture to 7.5-9.0;

[0144] Under nitrogen protection, monomer premix II (36 parts) was added to the reactor and the reaction temperature was maintained at 80° C. for 2 to 3 hours.

[0145] A pH regulator (0.1 part) was added to the reactor to adjust the pH of the mixture to 7.5-9.0;

[0146] The temperature of the reactor was lowered to below 35° C., sterilized, filtered, and discharged to obtain a water-based acrylic emulsion.

[0147] Exemplarily, the emulsifier is an anionic or nonionic emulsifier, selected from one or more of potassium laurate, potassium stearate, potassium oleate, sodium decyl sulfate, sodium lauryl sulfate, sodium dodecylbenzenesulfonate, sodium rosinate, and the like.

[0148] Exemplarily, the initiator is a water-soluble initiator selected from one or more of ammonium persulfate, sodium persulfate, potassium persulfate, tert-butyl hydroperoxide, and the like.

[0149] Exemplarily, the pH adjuster is an organic amine, selected from one or more of N,N-dimethylethanolamine, N,N-diethylethanolamine, 2-(dimethyl)amino-2-methyl-1-propanol, triethylamine, and the like.

[0150] The prepared water-based acrylic emulsion has a solid content of 45% to 55%, a hydroxyl value of 5 to 20 mgKOH / g, an acid value of 10 to 25 mgKOH / g, a resin particle size of 110 to 160 nm, and an emulsion pH of 7.5 to 9.0.

[0151] Unless otherwise specified, the aqueous polyurethane dispersion B used in the following examples was prepared by the following method:

[0152] (1) Synthesis and preparation of polyester polyols:

[0153] Under nitrogen protection, neopentyl glycol (7.5 parts), 1,6-hexanediol (38.5 parts), and 1,6-hexanediol (54 parts) were added to the reactor in sequence, and the temperature was raised to 120° C. until the raw materials melted;

[0154] After the raw materials are completely melted and mixed, continue stirring and heat to 160°C, hold for 1 hour, and then continue to heat to 230°C for 5 hours; during the heat preservation at 230°C, regularly test the acid value until the acid value drops below 1mgKOH / g;

[0155] The temperature is lowered to below 80°C to obtain polyester polyol.

[0156] The prepared polyester polyol has a hydroxyl value of 25-75 mgKOH / g, an acid value of less than 1 mgKOH / g, and a number average molecular weight of 1500-4000.

[0157] (2) Synthesis and preparation of polyurethane prepolymer dispersion:

[0158] Under nitrogen protection, the polyester polyol prepared above (34 parts) and the triol containing a carboxyl functional group (2.5 parts) were added to the reactor in sequence, and the mixture was stirred and heated to 80°C;

[0159] While maintaining the reaction temperature at 80°C, add non-aromatic diisocyanate (12 parts) and continue the reaction at 80°C until the NCO equivalent reaches 800-1100;

[0160] The temperature was lowered to 50° C., and triethylamine (2 parts) was added for neutralization. After sufficient neutralization, water (49.5 parts) was added to obtain a polyurethane prepolymer dispersion (NCO-terminated).

[0161] For example, the triol containing a carboxyl functional group is selected from one or more of trimethylol propionic acid (DMPA) and trimethylol butyric acid (DMBA).

[0162] For example, the non-aromatic diisocyanate is selected from one or more of isophorone diisocyanate (IPDI), hexamethylene diisocyanate (HDI), trimethylhexamethylene diisocyanate (TMDI), and dicyclohexylmethane diisocyanate (HMDI).

[0163] (3) Synthesis and preparation of polyurethane prepolymer dispersion:

[0164] Under nitrogen protection, the polyurethane prepolymer dispersion (83.2 parts), ethylenediamine (0.8 parts), and water (16 parts) prepared above were added to the reactor in sequence, and the mixture was stirred and heated to 60° C. for constant temperature reaction for 1 to 2 hours until the prepolymer chain extension reaction was completed;

[0165] The temperature was lowered to 40° C., and the mixture was filtered and discharged to obtain aqueous polyurethane dispersion B.

[0166] The prepared waterborne polyurethane B has a solid content of 32% to 42%, a hydroxyl value of less than 5 mgKOH / g, an acid value of 20 to 35 mgKOH / g, a number average molecular weight of more than 10,000, a resin particle size of 30 to 100 nm, and a dispersion pH of 7.0 to 8.5.

[0167] Preparation of three-coat and one-bake paint (BC) for automobiles:

[0168] The formula components of the three-coat and one-bake paint (BC) for automobiles are shown in Table 1:

[0169] Table 1

[0170]

[0171]

[0172] As described in Table 1 U 2750, U 2757 was purchased from Covestro (China) Co., Ltd.

[0173] As described in Table 1 TW 6466 / 36WA, 325 was purchased from Allnex Resins (Shanghai) Co., Ltd.

[0174] The components of the effect pigment slurry described in Table 1 include: 15 parts by weight of Aluminum Paste STAPA Metallux 2153 aluminum powder (purchased from Aika Special Effect Pigments Trading (Shanghai) Co., Ltd.), 5 parts by weight of AutomotiveRutile Fine White A-903D-SP pearlescent powder (purchased from CQV Co., Ltd.), 6 parts by weight of Dazzling Blue A-781S blue pearlescent powder (purchased from CQV Co., Ltd.), 9 parts by weight of LUBRIZOL 2062 passivator (purchased from Lubrizol Specialty Chemical Manufacturing (Shanghai) Co., Ltd.), 6407 (purchased from Allnex Resins (China) Co., Ltd.) 17 parts, ethylene glycol butyl ether 26 parts, n-propanol 12 parts, water 10 parts.

[0175] The blue pigment paste described in Table 1 is selected from the NAPER WF series blue paste of Bang Paint (China) Co., Ltd.

[0176] As described in Table 1 ST 2400, AS 1130 was purchased from BASF New Materials Co., Ltd.

[0177] The preparation process steps of the three-coat and one-bake paint (BC) for automobiles are as follows:

[0178] 1) Preparation of aluminum powder & pearlescent effect pigment slurry

[0179] Aluminum Paste STAPA Metallux 2153 aluminum powder, Automotive Rutile FineWhite A-903D-SP pearlescent powder, Dazzling Blue A-781S blue pearlescent powder, n-propyl alcohol and ethylene glycol butyl ether were soaked in a static state, and then stirred and mixed evenly under high-speed dispersion conditions. Then, LUBRIZOL 2062 passivator was added and stirred continuously to form a suspension of aluminum powder and pearlescent powder in the solvent. Finally, the mixture was added under high-speed stirring. 6407 resin, after being fully stirred, forms a stable aluminum powder & pearlescent effect pigment paste.

[0180] 2) Preparation of three-coat and one-bake paint (BC) for automobiles

[0181] Water-based acrylic emulsion, U 2750 resin, After U 2757 resin is stirred and mixed, continue to add 325 and stir well to mix, then add the aluminum powder & pearlescent powder effect pigment paste prepared above, stir at high speed to mix evenly, then add ST 2400 defoamer, ethylene glycol butyl ether, dipropylene glycol butyl ether, isooctyl alcohol, NAPER WF series blue paste, water, and finally add AS1130 rheological additive is stirred and mixed evenly to obtain a three-coat and one-bake paint (BC) for automobiles.

[0182] After the preparation of the paint BC product, it is diluted with water to 165-185 mPa.s, 23 ° C, 250 sec -1 Viscosity. The viscosity is measured by a rotary viscometer R-180. The test method is: 23°C, 2# rotor / 2# sleeve, 1000 sec. -1 Shear rate, 180 seconds, then 250 seconds -1 shear rate, 60s.

[0183] Preparation example of mid-coat preparation:

[0184] Preparation of three-coat-one-bake intermediate coatings 1 to 3 (PR1 to PR3) for automobiles:

[0185] The formula components of the three-coat-one-bake intermediate coatings 1 to 3 (PR1 to PR3) for automobiles are shown in Table 2:

[0186] Table 2

[0187]

[0188] As described in Table 2 OH 8312 is a water-based acrylic emulsion resin purchased from BASF Applied Chemicals Co., Ltd., with a solid content of 42% to 48%, a hydroxyl value of 90 mg to 110 mg KOH / g, an acid value of <10 mg KOH / g, and an emulsion pH of 7.0 to 8.0.

[0189] As described in Table 2 U XP 2755 / 1, U 2766 was purchased from Covestro (China) Co., Ltd.

[0190] LAPONITE RD described in Table 2 was purchased from BYK Chemical (China) Co., Ltd.

[0191] As described in Table 2 W2N was purchased from Leifuss (Shanghai) Chemical Trading Co., Ltd.

[0192] The NAPER WF CR-97 white paste described in Table 2 is selected from the NAPER WF series white paste of Nippon Paint (China) Co., Ltd.; its formula components include: 70 parts of TIPAQUE CR-97 titanium dioxide (purchased from Ishihara Sangyo Co., Ltd.), 8 parts of DISPERBYK-190 dispersant (purchased from BYK Chemical (China) Co., Ltd.), and 22 parts of water.

[0193] The preparation process steps of the three-coat-one-bake intermediate paints 1 to 3 (PR1 to PR3) for automobiles are as follows:

[0194] 1) Preparation of inorganic silicate rheological additive dispersion

[0195] Under high-speed stirring conditions, LAPONITE RD powder (3 parts) or Add W2N powder (3 parts) to water (90 parts), continue stirring for 1 to 2 hours, then let it stand at room temperature for 10 to 12 hours, then add polypropylene glycol (3 parts) and water (4 parts) under high-speed stirring. Continue stirring for 1 hour, then let it stand at room temperature for 10 to 12 hours to obtain LAPONITE RD dispersion (or W2N dispersion).

[0196] 2) Preparation of NAPER WF CR-97 white pulp

[0197] After pre-mixing TIPAQUE CR-97 titanium dioxide, DISPERBYK-190 dispersant, and water, add abrasive beads such as glass beads or zirconium beads in a sand mill and grind and disperse until the fineness reaches less than 5 microns to obtain NAPER WF CR-97 white slurry.

[0198] 3) Preparation of automotive three-coat and one-bake intermediate paints 1 to 3 (PR1 to PR3)

[0199] Under high-speed stirring conditions, the water-based acrylic emulsion (or OH 8312) and LAPONITE RD dispersion (or W2N dispersion) and mix thoroughly; then add waterborne polyurethane dispersion B, U XP 2755 / 1 (or U 2766) and stirred for about 0.5 hours; then continue to add NAPERWF CR-97 white slurry and stir for 0.5 to 1 hour to fully mix and disperse; continue to add 325、FOA ST 2400 defoamer, ethylene glycol butyl ether, isopropyl alcohol, isooctanol, dipropylene glycol butyl ether, water; finally add AS 1130 rheological additive is stirred and mixed evenly to obtain automotive three-coat and one-bake intermediate coatings 1 to 3 (PR1 to PR3).

[0200] After the preparation of the intermediate coatings 1 to 3 (PR1 to PR3), the intermediate coatings 1 to 3 (PR1 to PR3) were diluted with water to 160 to 190 mPa.s at 23°C for 250 seconds. -1 Viscosity. The viscosity is measured by a rotary viscometer R-180. The test method is: 23°C, 2# rotor / 2# sleeve, 1000 sec. -1 Shear rate, 180 seconds, then 250 seconds -1 shear rate, 60s.

[0201] Preparation of three-coat-one-bake intermediate paint 4 to 6 (PR4 to PR6) for automobiles:

[0202] The formula components of the three-coat-one-bake intermediate paints 4 to 6 (PR4 to PR6) for automobiles are shown in Table 3:

[0203] Table 3

[0204]

[0205] As described in Table 3 UH 2557 is a water-based polyurethane dispersion purchased from Covestro (China) Co., Ltd. with a solid content of 34% to 38%, a hydroxyl value of <5 mgKOH / g, an acid value of <5 mgKOH / g, a resin particle size of 50 to 90 nm, and an emulsion pH of 6.5 to 8.5.

[0206] The preparation process steps of the three-coat-one-bake intermediate paints 4 to 6 (PR4 to PR6) for automobiles are as follows:

[0207] 1) Preparation of LAPONITE RD dispersion

[0208] The preparation method is the same as the preparation method of the inorganic silicate rheological additive dispersion in the mid-coat paints 1 to 3 (PR1 to PR3).

[0209] 2) Preparation of NAPER WF CR-97 white pulp

[0210] The preparation method is the same as that of NAPER WF CR-97 white paste in mid-coat paints 1 to 3 (PR1 to PR3).

[0211] 3) Preparation of automotive three-coat and one-bake intermediate paints 4 to 6 (PR4 to PR6)

[0212] Under high-speed stirring conditions, the aqueous acrylic emulsion and LAPONITE RD dispersion were fully mixed; then the aqueous polyurethane dispersion B (or UH 2557), U XP 2755 / 1 and stir for about 0.5 hours; then continue to add NAPER WF CR-97 white paste and stir for 0.5 to 1 hour to fully mix and disperse; continue to add 325, ST 2400 defoamer, ethylene glycol butyl ether, isopropyl alcohol, isooctanol, dipropylene glycol butyl ether, water; finally add AS 1130 rheological additive is stirred and mixed evenly to obtain automotive three-coat and one-bake intermediate paints 4 to 6 (PR4 to PR6).

[0213] After the preparation of the intermediate paints 4 to 6 (PR4 to PR6), dilute with water to 160 to 190 mPa.s at 23°C for 250 seconds. -1 Viscosity. The viscosity is measured by a rotary viscometer R-180. The test method is: 23°C, 2# rotor / 2# sleeve, 1000 sec. -1 Shear rate, 180 seconds, then 250 seconds -1 shear rate, 60s.

[0214] Preparation of three-coat-one-bake intermediate paint 7 to 9 (PR7 to PR9) for automobiles:

[0215] The formula components of the three-coat-one-bake intermediate paints 7 to 9 (PR7 to PR9) for automobiles are shown in Table 4:

[0216] Table 4

[0217]

[0218] As described in Table 4 U 2757 is a waterborne polyurethane dispersion purchased from Covestro (China) Co., Ltd., with a solid content of 45% to 55%, a hydroxyl value of 30 to 70 mgKOH / g, an acid value of <10 mgKOH / g, a resin particle size of 90 to 120 nm, and an emulsion pH of 7.0 to 8.5.

[0219] The preparation process steps of the three-coat-one-bake intermediate paint 7 to 9 (PR7 to PR9) for automobiles are as follows:

[0220] 1) Preparation of inorganic silicate rheological additive dispersion

[0221] The preparation method is the same as the preparation method of the inorganic silicate rheological additive dispersion in the mid-coat paints 1 to 3 (PR1 to PR3).

[0222] 2) Preparation of NAPER WF CR-97 white pulp

[0223] The preparation method is the same as that of NAPER WF CR-97 white paste in mid-coat paints 1 to 3 (PR1 to PR3).

[0224] 3) Preparation of automotive three-coat and one-bake intermediate paint 7 to 9 (PR7 to PR9)

[0225] Under high-speed stirring conditions, water-based acrylic emulsion and LAPONITE RD dispersion (or W2N dispersion) and mix thoroughly; then add waterborne polyurethane dispersion B, U XP 2755 / 1 (or U 2766, or U 2757) and stirred for about 0.5 hours; then continue to add NAPER WFCR-97 white slurry and stir for 0.5 to 1 hour to fully mix and disperse; continue to add 325、FOAM- ST 2400 defoamer, ethylene glycol butyl ether, isopropyl alcohol, isooctanol, dipropylene glycol butyl ether, water; finally add AS 1130 rheological additive is stirred and mixed evenly to obtain automotive three-coat and one-bake intermediate paint 7 to 9 (PR7 to PR9).

[0226] After the preparation of the intermediate paints 7 to 9 (PR7 to PR9), dilute with water to 160 to 190 mPa.s at 23°C for 250 seconds. -1 Viscosity. The viscosity is measured by a rotary viscometer R-180. The test method is: 23°C, 2# rotor / 2# sleeve, 1000 sec. -1 Shear rate, 180 seconds, then 250 seconds -1 shear rate, 60s.

[0227] Preparation of three-coat-one-bake mid-coat paint 10-12 (PR10-PR12) for automobiles:

[0228] The formula components of the automotive three-coat and one-bake intermediate paint 10-12 (PR10-PR12) are shown in Table 5:

[0229] Table 5

[0230]

[0231]

[0232] As described in Table 5. EW NA is hectorite clay purchased from Deqian (Shanghai) Chemical Co., Ltd. Its chemical elements include silicon, magnesium, lithium, sodium, etc., and its basic structural unit morphology is a flat rectangular thin-plate crystal with a particle size of 80nm×800nm×1nm.

[0233] The preparation process steps of the automotive three-coat and one-bake intermediate paint 10-12 (PR10-PR12) are as follows:

[0234] 1) Preparation of inorganic silicate rheological additive dispersion

[0235] Under high-speed stirring conditions, LAPONITE RD powder (3 parts) (or W2N powder (3 parts), or Add EW NA powder (3 parts) to water (90 parts), continue stirring for 1 to 2 hours and then let it stand at room temperature for 10 to 12 hours, then add polypropylene glycol (3 parts) and water (4 parts) under high-speed stirring. Continue stirring for 1 hour and then let it stand at room temperature for 10 to 12 hours to obtain LAPONITE RD dispersion (or W2N dispersion, or EW NA dispersion).

[0236] 2) Preparation of NAPER WF CR-97 white pulp

[0237] The preparation method is the same as that of NAPER WF CR-97 white paste in mid-coat paints 1 to 3 (PR1 to PR3).

[0238] 3) Preparation of automotive three-coat and one-bake intermediate paint 10-12 (PR10-PR12)

[0239] Under high-speed stirring conditions, water-based acrylic emulsion and LAPONITE RD dispersion (or W2N dispersion, or EW NA dispersion) and mix thoroughly; then add waterborne polyurethane dispersion B, U XP 2755 / 1 (or U 2766) and stirred for about 0.5 hours; then continue to add NAPERWF CR-97 white slurry and stir for 0.5 to 1 hour to fully mix and disperse; continue to add 325, ST 2400 defoamer, ethylene glycol butyl ether, isopropyl alcohol, isooctanol, dipropylene glycol butyl ether, water; finally add AS 1130 rheological additive is stirred and mixed evenly to obtain automotive three-coat and one-bake intermediate paint 10-12 (PR10-PR12).

[0240] After the preparation of the intermediate paints 10 to 12 (PR10 to PR12), dilute with water to 160 to 190 mPa.s at 23°C for 250 seconds. -1 Viscosity. The viscosity is measured by a rotary viscometer R-180. The test method is: 23°C, 2# rotor / 2# sleeve, 1000 sec. -1 Shear rate, 180 seconds, then 250 seconds -1 shear rate, 60s.

[0241] Application Examples

[0242] Examples 1 to 8

[0243] The spraying plate making method of Examples 1 to 8 of the present invention is as follows:

[0244] Electrophoretic paint PN-310 (from Nippon Paint (China) Co., Ltd.) was applied to the surface of the passivated steel plate treated with zinc phosphate, and then baked at 160°C for 30 minutes to form the required substrate plate (the dry film thickness of the electrophoretic paint coating was 19 to 24 microns).

[0245] The spraying operation was performed using a LACTEC automatic spray robot equipped with a DURR atomizer: the aforementioned midcoat (the aforementioned automotive three-coat, one-bake midcoat: PR1-2, PR4-5, PR7-8, PR10-11) was first sprayed onto the surface of the substrate, and flashed off for 6 minutes at room temperature of 21-25°C and humidity of 65±5% RH; then the first coat of basecoat (the aforementioned automotive three-coat, one-bake basecoat: BC) was sprayed, and flashed off for 90 seconds at room temperature of 21-25°C and humidity of 65±5% RH; then the second coat of basecoat (the aforementioned automotive three-coat, one-bake basecoat: BC) was sprayed, and flashed off for 2 minutes at room temperature of 21-25°C and humidity of 65±5% RH; then the sample (substrate / midcoat / basecoat) was pre-baked in an oven at 80°C for 8 minutes, the pre-baked sample was removed, and cooled to room temperature of 21-25°C. Next, the sample surface was sprayed with a varnish mixture (varnish: CLEARCOAT PU 2K HD II varnish, curing agent: HARDENER for 2K HD (75%), varnish: curing agent = 3:1 (weight ratio); varnish and curing agent both from Nippon Paint (China) Co., Ltd.) and flash-dried for 8 minutes at room temperature (21-25°C) and humidity (65±5% RH). Finally, the prepared sample (substrate plate / midcoat / color paint / varnish) was placed in an oven and baked at a high temperature of 140°C for 30 minutes. The baked sample was removed and cooled to room temperature (21-25°C).

[0246] For the testing of coating appearance, paint film mechanical properties and other properties, the dry film thickness of each coating of the prepared sample (substrate board / midcoat / color paint / clear coat) is: midcoat layer: 12-16 microns, first topcoat layer: 7-9 microns, second topcoat layer: 7-9 microns, clear coat: 45-55 microns.

[0247] For the testing of construction application performance such as sagging limit film thickness and pinhole limit film thickness, the dry film thickness of each coating of the prepared sample (substrate board / midcoat / color paint / clear coat) is: midcoat layer: 12-16 microns, first topcoat layer: 5-40 microns, second topcoat layer: 5-40 microns, clear coat: 45-55 microns.

[0248] Specifically, the coating structures (midcoat / color paint / clear coat) of Examples 1 to 4 are shown in Table 6:

[0249] Table 6

[0250]

[0251] Specifically, the coating structures (midcoat / color paint / clear coat) of Examples 5 to 8 are shown in Table 7.

[0252] Table 7

[0253]

[0254] Comparative Examples 1 to 4

[0255] The spraying and board-making methods of Comparative Examples 1 to 4 of the present invention are the same as those of Examples 1 to 8, with the only difference being that the mid-coat paint used (the aforementioned three-coat and one-bake mid-coat paint for automobiles: PR1 to 2, PR4 to 5, PR7 to 8, and PR10 to 11) is replaced with a mid-coat paint (the aforementioned three-coat and one-bake mid-coat paint for automobiles: PR3, PR6, PR9, and PR12).

[0256] Specifically, the coating structures (midcoat / color paint / clear coat) of Comparative Examples 1 to 4 are shown in Table 8:

[0257] Table 8

[0258]

[0259]

[0260] Solid content and VOC determination

[0261] The test results of the solid content and VOC (coating organic solvent content (excluding water)) of the mid-coat paint (PR1-2, PR4-5, PR7-8, PR10-11) samples used in Examples 1-8 of the present invention are shown in Table 9:

[0262] Table 9

[0263]

[0264] It can be inferred from the test data in Table 9 that the mid-coat paints (PR1-2, PR4-5, PR7-8, PR10-11) used in Examples 1-8 of the present invention all have a higher solid content (>41%) and a lower VOC content (<140 g / L).

[0265] Coating appearance test

[0266] The appearance data of the full coating of the samples of Examples 1 to 4 and Comparative Examples 1 to 2 of the present invention are shown in Table 10:

[0267] Table 10

[0268]

[0269]

[0270] The appearance data of the full coating of the samples of Examples 5 to 8 and Comparative Examples 3 to 4 of the present invention are shown in Table 11:

[0271] Table 11

[0272]

[0273] After analyzing the full coating appearance data in Tables 10 and 11, it can be inferred that:

[0274] 1) Example 1 / Example 2 Compared with Comparative Example 1, the acrylic emulsion resin in the paint formula component is OH 8312 emulsion (solid content of 42% to 48%, hydroxyl value of 90mg to 110mgKOH / g, acid value of <10mgKOH / g, emulsion pH of 7.0 to 8.0) was replaced with the water-based acrylic emulsion described in this patent (solid content of 45% to 55%, hydroxyl value of 5 to 20mgKOH / g, acid value of 10 to 25mgKOH / g, emulsion pH of 7.5 to 9.0); OH 8312 emulsion resin and the acrylic emulsion resin described in this patent have the same hydroxyl value ( OH 8312 emulsion: 90mg~110mgKOH / g; acrylic emulsion described in this patent: 5~20mgKOH / g), acid value ( There are differences in physical properties (OH 8312 emulsion: <10 mgKOH / g; acrylic emulsion described in this patent: 10-25 mgKOH / g). Comparing the appearance data in Table 10, it can be seen that the horizontal and vertical appearance data (long wave (LW), short wave (LW), distinctness of image (DOI)) of Example 1 and Example 2 are better than those of Comparative Example 1.

[0275] 2) Example 3 / Example 4 Compared with Comparative Example 2, the polyurethane dispersion in the paint formulation components is UH 2557 (solid content 34%-38%, hydroxyl value <5 mgKOH / g, acid value <5 mgKOH / g, resin particle size 50-90 nm, dispersion pH 6.5-8.5) was replaced with waterborne polyurethane dispersion B (solid content 32%-42%, hydroxyl value <5 mgKOH / g, acid value 20-35 mgKOH / g, resin particle size 30-100 nm, dispersion pH 7.0-8.5); UH 2557 resin and polyurethane dispersion B described in this patent have the following characteristics: There are differences in physical properties (UH 2557 resin: <5 mgKOH / g; polyurethane dispersion B described in this patent: 20-35 mgKOH / g). Comparing the appearance data in Table 10, it can be seen that the horizontal and vertical appearance data (long wave (LW), short wave (LW), distinctness of image (DOI)) of Example 3 and Example 4 are better than those of Comparative Example 2.

[0276] 3) Example 5 / Example 6 Compared with Comparative Example 3, the polyurethane dispersion in the paint formulation components is U 2757 (solid content 45% to 55%, hydroxyl value 30 to 70 mgKOH / g, emulsion pH 7.0 to 8.5) was replaced with U XP 2755 / 1 or U 2766 (solid content 34% to 44%, hydroxyl value 110 to 160 mgKOH / g, dispersion pH 7.0 to 8.8); U 2757 resin and the patent UXP 2755 / 1 or U 2766 resin has a hydroxyl value ( UH 2557 resin: 30-70 mgKOH / g; U XP 2755 / 1 or There are differences in physical properties such as U 2766 resin (110-160 mgKOH / g). Comparing the appearance data in Table 10, it can be seen that the horizontal and vertical appearance data (long wave (LW), short wave (LW), and distinctness of image (DOI)) of Example 5 / Example 6 are better than those of Comparative Example 3.

[0277] 4) Example 7 / Example 8 Compared with Comparative Example 4, the inorganic silicate rheological additive in the mid-coat paint formula component is EW NA (microstructure unit morphology is a flat rectangular thin plate crystal with a front length and width of 800nm×80nm and a side thickness of 1nm, with hydroxyl functional groups) is replaced with LAPONITE RD or W2N (microstructure unit morphology is a flat cylindrical thin crystalline body with a front diameter of 20-40 nm and negative charge, and a side thickness of 0.5-2.5 nm and positive charge); EW NA and LAPONITE RD or W2N in microstructure unit morphology ( EW NA: flat rectangular shaped crystalline flakes (with hydroxyl functional groups on the side); LAPONITE RD or W2N: Oblate cylindrical flaky crystals (positively charged on the sides). Comparing the appearance data in Table 10, the horizontal and vertical appearance data (long wave (LW), short wave (LW), and distinctness of image (DOI)) of Examples 7 and 8 are better than those of Comparative Example 4.

[0278] Mechanical properties of coating films and construction application tests

[0279] The test data of the paint film mechanical properties (stone chip resistance, hardness) and construction applicability (sagging limit film thickness, pinhole limit film thickness) of Examples 1 to 4 and Comparative Examples 1 to 2 of the present invention are shown in Table 12:

[0280] Table 12

[0281]

[0282]

[0283] The test data of the paint film mechanical properties (stone chip resistance, hardness) and construction applicability (sagging limit film thickness, pinhole limit film thickness) of Examples 5 to 8 and Comparative Examples 3 to 4 of the present invention are shown in Table 13:

[0284] Table 13

[0285]

[0286] After analyzing the mechanical properties and construction applicability data of the full coating film in Tables 12 and 13, it can be inferred that:

[0287] 1) Example 1 / Example 2 Compared with Comparative Example 1, the acrylic emulsion resin in the paint formula component is When OH 8312 is replaced with the water-based acrylic emulsion described in this patent, its sagging limit film thickness and pinhole limit film thickness are significantly improved.

[0288] 2) Example 3 / Example 4 Compared with Comparative Example 2, the polyurethane dispersion in the paint formulation components is When UH 2557 was replaced with waterborne polyurethane dispersion B, the stone chip resistance of the coating was significantly improved.

[0289] 3) Example 5 / Example 6 Compared with Comparative Example 3, the polyurethane dispersion in the paint formulation components is U 2757 replaced by U XP 2755 / 1 (or U 2766), the coating hardness and stone impact resistance are significantly improved.

[0290] Example 7 / Example 8 Compared with Comparative Example 4, the inorganic silicate rheological additive in the mid-coat formulation is EW NA replaced with LAPONITE RD (or W2N), its sagging limit film thickness and pinhole limit film thickness are significantly improved.

[0291] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not limitations on the implementation methods of the present invention. For ordinary technicians in the relevant field, other different forms of changes or modifications can be made based on the above description. It is impossible to list all the implementation methods here. All obvious changes or modifications derived from the technical solution of the present invention are still within the scope of protection of the present invention.

Claims

1. A high-solid, three-coat, one-bake mid-coat for automobiles based on waterborne acrylic resin, characterized in that: The mid-coat paint is a single-component paint, and comprises the following components in parts by weight: 10-25 parts of aqueous acrylic emulsion, 5-15 parts of aqueous polyurethane dispersion B, 5-15 parts of aqueous polyurethane dispersion C and 30.1-70.4 parts of additives; in: The additive contains 0.1 to 0.4 parts of an inorganic rheological additive; The aqueous polyurethane dispersion B has a solid content of 32% to 42%, a hydroxyl value of <5 mgKOH / g, an acid value of 20 to 35 mgKOH / g, a number average molecular weight of >10,000, a resin particle size of 30 to 100 nm, and a dispersion pH of 7.0 to 8.5; The solid content of the aqueous polyurethane dispersion C is 34% to 44%, the hydroxyl value is 110 to 160 mgKOH / g, and the dispersion pH is 7.0 to 8.8; The water-based acrylic emulsion has a solid content of 45% to 55%, a hydroxyl value of 5 to 20 mgKOH / g, an acid value of 10 to 25 mgKOH / g, a resin particle size of 110 to 160 nm, and an emulsion pH of 7.5 to 9.0; The inorganic rheological additive is an inorganic sheet silicate.

2. The high-solid three-coat-one-bake intermediate paint for automobiles according to claim 1, characterized in that: The aqueous acrylic emulsion is prepared from acrylic acid monomers, acrylate monomers, methacrylate monomers and vinyl monomers through free radical emulsion polymerization.

3. The high-solid three-coat-one-bake intermediate paint for automobiles according to claim 2, characterized in that: The preparation of the aqueous acrylic emulsion specifically comprises the following steps: Premixing acrylic monomers, part of acrylic ester monomers, part of methacrylic ester monomers, and part of vinyl monomers in the presence of water and an emulsifier to obtain a monomer premix solution I; Premixing the remaining acrylic acid ester monomer, the remaining methacrylic acid ester monomer, and the remaining vinyl monomer in the presence of water and an emulsifier to obtain a monomer premix solution II; Under nitrogen protection, the monomer premix solution I was subjected to a prepolymerization reaction and the pH was adjusted to 7.5-9.0; The monomer premix II is continuously added to the resultant to carry out polymerization reaction, and the pH is adjusted to 7.5-9.0 to obtain the aqueous acrylic emulsion.

4. The high-solid three-coat-one-bake intermediate paint for automobiles according to claim 1, characterized in that: The aqueous polyurethane dispersion B is prepared by reacting materials including polyester polyol, non-aromatic diisocyanate, and triol containing a carboxyl functional group.

5. The high-solid three-coat-one-bake intermediate paint for automobiles according to claim 4, characterized in that: The preparation of the aqueous polyurethane dispersion B specifically comprises the following steps: Synthetic polyester polyols with a hydroxyl value of 25~75mgKOH / g, an acid value <1mgKOH / g, and a number average molecular weight of 1500~4000; Under nitrogen protection, the polyester polyol and the triol containing a carboxyl functional group are mixed, and then reacted with a non-aromatic diisocyanate until the NCO equivalent reaches 800 to 1100; after neutralization, a polyurethane prepolymer dispersion is obtained; Under nitrogen protection, the polyurethane prepolymer dispersion is subjected to a chain extension reaction to obtain the aqueous polyurethane dispersion B.

6. The high-solid three-coat-one-bake intermediate paint for automobiles according to claim 1, characterized in that: The inorganic sheet silicate has a trioctahedral crystal structure, and the basic structural unit morphology is an oblate cylindrical thin-plate crystal with a front diameter of 20-40 nm and a negative charge, and a side thickness of 0.5-2.5 nm and a positive charge.

7. The high-solid three-coat-one-bake intermediate paint for automobiles according to claim 1, characterized in that: The additives further comprise: 5 to 10 parts of a film-forming solvent, 0.5 to 2 parts of an organic rheological additive, 2 to 4 parts of a defoaming agent, and 1 to 3 parts of a dispersant.

8. The high-solid three-coat-one-bake intermediate paint for automobiles according to claim 1, characterized in that: The mid-coat paint further comprises 5 to 15 parts of amino resin, 15 to 25 parts of pigments and fillers, and 5 to 20 parts of water.

9. Use of the high-solid three-coat-one-bake intermediate coating for automobiles according to any one of claims 1 to 8 in forming an automobile coating.

10. The use according to claim 9, characterized in that The steps include: Applying the mid-coat on the electrophoretic primer coating; Flash dry to form a midcoat.